1995
DOI: 10.1115/1.2836579
|View full text |Cite
|
Sign up to set email alerts
|

On Fast-Response Probes: Part 1—Technology, Calibration, and Application to Turbomachinery

Abstract: A system for fast-response probe measurements in turbomachine flows has been developed and tested. The system has been designed for 40 kHz bandwidth and used with various in-house built probes accommodating up to four piezoresistive pressure transducers. The present generation of probes works accurately up to several bar pressure and 120°C temperature. The probes were found to be quite robust. The use of a miniature pressure transducer placed in the head of a probe showed that a precise packaging technique and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 3 publications
1
18
0
1
Order By: Relevance
“…The configuration of the system used for the measurements presented herein has been described in detail in reference [13]. A more general overview has been given in reference [14]. In the following the main features of the system will be described briefly.…”
Section: Fast-response Probe System (Frap ® )mentioning
confidence: 99%
“…The configuration of the system used for the measurements presented herein has been described in detail in reference [13]. A more general overview has been given in reference [14]. In the following the main features of the system will be described briefly.…”
Section: Fast-response Probe System (Frap ® )mentioning
confidence: 99%
“…[27] ffir ihre Str6mungsmessungen eine Ffinf-Loch-Sonde ein, bei der die Drucksensoren im Sondenschaft (Q = 9.14 ram) angeordnet waren. Besonders hervorzuheben sind die Arbeiten yon Gossweiler [17,18,19], in denen die Entwicklung yon Ein-Sensor-und Vier-Sensor-Sonden mit kleinsten Abmessungen sowie die Eignung yon Siliziumhalbleitern for die instation/ire Str6mungsmessung beschrieben werden.…”
Section: Entwicklungsstand Und Problemstellungunclassified
“…The FRAPP concept comes from the combination of fast-response pressure transducers, typically of the piezoresistive kind, with aerodynamic directional pressure probes. The transducers can be flush-mounted on the probe head [14], enhancing the frequency response despite fragility; in other examples [6,[15][16][17], the researchers preferred to embed the transducers within the probe head to enhance the probe strength. Excellent reviews on the early stages of FRAPP development can be found in [18][19][20].…”
Section: Introductionmentioning
confidence: 99%